Intestinal invalidation of the glucose transporter GLUT2 delays tissue distribution of glucose and reveals an unexpected role in gut homeostasis - Charlotte C. Schmitt; Thomas Aranias; Thomas Viel; Danielle Chateau; Maude Le Gall; Anne-Judith Wa; Chloé Melchior; Ophélie Rouxel; Nathalie Kapel; Guillaume Gourcerol; Bertrand Tavitian; Agnès Lehuen; et al. (Elsevier, 2017)
Objective: Intestinal glucose absorption is orchestrated by specialized glucose transporters such as SGLT1 and GLUT2. However, the role of GLUT2 in the regulation of glucose absorption remains to be fully elucidated. Methods: We wanted to evaluate the role of GLUT2 on glucose absorption and glucose homeostasis after intestinal-specific deletion of GLUT2 in mice (GLUT2ΔIEC mice). Results: As anticipated, intestinal GLUT2 deletion provoked glucose malabsorption as visualized by the delay in the distribution of oral sugar in tissues. Consequences of intestinal GLUT2 deletion in GLUT2ΔIEC mice were limiting body weight gain despite normal food intake, improving glucose tolerance, and increasing ketone body production. These features were reminiscent of calorie restriction. Other adaptations to intestinal GLUT2 deletion were reduced microvillus length and altered gut microbiota composition, which was associated with improved inflammatory status. Moreover, a reduced density of glucagon-like peptide-1 (GLP-1) positive cells was compensated by increased GLP-1 content per L-cell, suggesting a preserved enteroendocrine function in GLUT2ΔIEC mice. Conclusions: Intestinal GLUT2 modulates glucose absorption and constitutes a control step for the distribution of dietary sugar to tissues. Consequently, metabolic and gut homeostasis are improved in the absence of functional GLUT2 in the intestine, thus mimicking calorie restriction. Author Video: Author Video Watch what authors say about their articles Keywords: Malabsorption, Glucose homeostasis, Intestinal adaptation, Microbiota, GLP-1